Subterranean Kerouac : the hidden life of Jack Kerouac - Amburn, Ellis (New York : St. Martin's Press, 1998)
Drawing upon original interviews, his own relationship with Kerouac, Kerouac's recently published letters, and still-unpublished journals from the Kerouac archives, Ellis Amburn reveals an inner Kerouac that has not appeared in any previous biography. This is the "subterranean" Kerouac whom Amburn, the editor of his last two novels, knew personally, having witnessed the legendary Beat writer's decline into alcoholic despair during the last few years of his life. Perhaps the greatest of Kerouac's conflicts centered around his sexual relationships with men. Amburn recounts what Kerouac himself told him about these experiences, which other biographers have never before reported, and sheds new light on their profound impact on the man who remained convinced until his death that he was not bisexual, and that homosexuality was in fact immoral
Climax Runner -- The Agonized Cock of the Matter -- Mad About the Boy -- Macho Manslaughter -- "The Road is Better Than the Inn" -- Muscles, Meat, and Metaphysics -- Sucking Asses to Get Published -- Orgasm, Buddhism, and the Art of Writing -- Success, Love, Marriage, Madness -- Starvation Ridge -- Touchdown -- Crack-Up -- A Personal Reminiscence
Includes bibliographical references (pages [389]-424) and index
Keywords: Kerouac, Jack, -- 1922-1969; Authors, American -- 20th century -- Biography; Beats (Persons) -- Biography